Implementation of Fuzzy Logic in Soil Moisture and Temperature Control System for Araceae Plants Based on LoRa - Salamah, Irma; Suzanzefi, Suzanzefi; Ningrum, Shinta Sulistiya (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
The Araceae plants are highly popular among plant enthusiasts worldwide. The Araceae family has more than 100 different types and thousands of species. Despite ever-evolving times, these plants have a high market value and challenging breeding methods. To achieve optimal quality, it is important to maintain the appropriate humidity and temperature according to the natural conditions of these plants in the tropical rainforest. The Node MCU ESP32 is a processor for instructions from the room temperature sensor, room humidity sensor, and soil moisture sensor. Additionally, this component controls the blower and misting system as output, which will be processed through LoRa technology to transmit monitoring data to the Blynk software. This study utilizes fuzzy logic to categorize room temperature, humidity, soil moisture, and output results for different Araceae plants. LoRa technology is used to send monitoring data efficiently in the data transmission process. During data retrieval using long-range technology, a delay of approximately 5 seconds is known between the receiver and transmitter at a distance of 700 meters. Constraints that cause issues with this long-range technology are influenced by wind, which affects antenna signal strength, and the presence of trees and buildings as obstacles. The monitoring results show an average temperature in normal conditions and an average humidity in wet conditions. At the same time, soil moisture is monitored to maintain normal humidity, resulting in all outputs being off.